Preparation of Black Carbon Nanoparticles from Two Sources of Oil Residues with Direct and Indirect Ultrasonic Process - Rusul Alsaffar; Balqees Al-Dabbagh; Hanaa Jawad (Journal of Applied Sciences and Nanotechnology, 2023)
In this work, two methods for creating carbon nanoparticles from oil waste or by products, which accumulate on pipes and Furnaces walls and reduce equipment efficiency and service life (that can hinder the production process, accordingly it is removed weekly) — are compared. These waste products or by products result from the incomplete burning of hydrocarbon compounds during crude oil refining to produce petroleum products. The raw materials had been gathered from two places from Al-Dura refinery, sieving, burned in furnace of atmosphere that was both vacuumed and inert, crushed by mortar and washed by solvent, washing by distilled water, drying then reduced to nanoparticle size using direct crushing (sonication by probe) and indirect ultrasonic (bath sonication) processes. The samples were examined using the relevant procedures, such as EDX and SEM, as well as tests following crushing and burning. Zeta potential and particle size analysis were two additional tests conduct on the final products. The results showed that after burning, the proportion of carbon increased from 28.49, 36.30 to 91.59, and 94.47 % sequentially. Also, the direct ultrasonic method is superior to the indirect method for manufacturing carbon nanoparticles, which required less time and able to produce nanoparticles with average granular sizes about 37 nm and 86.6 nm for the first and second samples, respectively. Zeta potential data proved the resulting Nano carbon particles are quite stable.